2021
DOI: 10.3390/cancers13205099
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Epithelial–Mesenchymal Transition on the Immune Landscape in Breast Cancer

Abstract: The impact of epithelial–mesenchymal transition (EMT) signature on the immune infiltrate present in the breast cancer tumor microenvironment (TME) is still poorly understood. Since there is mounting interest in the use of immunotherapy for the treatment of subsets of breast cancer patients, it is of major importance to understand the fundamental tumor characteristics which dictate the inter-tumor heterogeneity in immune landscapes. We aimed to assess the impact of EMT-related markers on the nature and magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 77 publications
2
8
0
Order By: Relevance
“…In contrast, epithelial states were largely dominant in the luminal A subtype [ 51 ]. Along similar lines, two other studies revealed that the mesenchymal markers N-cadherin and vimentin positively correlated with a higher histological grade and the absence of hormone receptors in breast tumors [ 52 , 53 ]. Thus, a loss of E-cadherin and gain of N-cadherin and vimentin has been reported in TNBCs, invasive lobular carcinomas and a subset of invasive ductal carcinomas [ 52 , 53 ].…”
Section: Emt As a Driver Of Resistance To Anti-tumor Immunitysupporting
confidence: 57%
See 1 more Smart Citation
“…In contrast, epithelial states were largely dominant in the luminal A subtype [ 51 ]. Along similar lines, two other studies revealed that the mesenchymal markers N-cadherin and vimentin positively correlated with a higher histological grade and the absence of hormone receptors in breast tumors [ 52 , 53 ]. Thus, a loss of E-cadherin and gain of N-cadherin and vimentin has been reported in TNBCs, invasive lobular carcinomas and a subset of invasive ductal carcinomas [ 52 , 53 ].…”
Section: Emt As a Driver Of Resistance To Anti-tumor Immunitysupporting
confidence: 57%
“…Importantly, many of these immune regulatory factors that are expressed by cancer cells undergoing an EMT are also indicative of poor prognosis of TNBCs. Moreover, a subset of TNBCs themselves, activate components of the EMT program [ 51 , 52 ]. This striking overlap of immune-regulatory factors that are expressed by cancer cells undergoing an EMT and by TNBC tumors, brings to the forefront the attractive possibility of using the EMT program as a parameter that can be (1) used as a predictive criterion for responses of breast tumors to immunotherapies and (2) intercepted to potentiate the susceptibility of breast tumors to immunotherapies.…”
Section: Emt As a Driver Of Resistance To Anti-tumor Immunitymentioning
confidence: 99%
“…Paraffin sections were dewaxed to water, antigenic repaired, endogenous peroxidase blocked, bovine serum albumin sealed and then co-cultured with primary antibody followed by incubation with secondary antibody [ 20 ]. DAB was used to color the slices and hematoxylin was used to re-stain the nuclei.…”
Section: Methodsmentioning
confidence: 99%
“…Tissue micro-arrays (TMAs) were prepared from cores (1 mm) extracted from each of 118 formalin-fixed and paraffin-embedded (FFPE) breast tumor tissues as previously described [ 53 ]. These samples were obtained from patients with primary breast tumors who underwent surgery at the Hôtel Dieu Hospital and at the Centre Hospitalier de l’Université de Montréal (CHUM) between 2001 and 2018.…”
Section: Methodsmentioning
confidence: 99%